2007
DOI: 10.1002/pola.22105
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and chiral recognition of optically active polymers containing pendent chiral units via reversible addition‐fragmentation chain transfer polymerization

Abstract: Optically active polymers bearing chiral units at the side chain were prepared via reversible addition‐fragmentation chain transfer (RAFT) polymerization in the presence of 2,2′‐azobisisobutyronitrile (AIBN)/benzyl dithiobenzoate (BDB), using a synthesized 6‐O‐p‐vinylbenzyl‐1,2:3,4‐Di‐O‐isopropylidene‐D‐galactopyranose (VBPG) as the monomer. The experimental results suggested that the polymerization of the monomer proceeded in a living fashion, providing chiral group polymers with narrow molecular weight distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
4
21
1
Order By: Relevance
“…Such kind of observations were also reported by Wang et al. for the optically active polymer poly(6‐ O ‐ p ‐vinylbenzyl‐1,2:3,4‐di‐ O ‐isopropylidene‐ d ‐galactopyranose) . Generally, the chiroptical properties of artificial polymers depend on several other factors such as the presence of stereoregular secondary structures and the chirality of the repeating units .…”
Section: Resultsmentioning
confidence: 99%
“…Such kind of observations were also reported by Wang et al. for the optically active polymer poly(6‐ O ‐ p ‐vinylbenzyl‐1,2:3,4‐di‐ O ‐isopropylidene‐ d ‐galactopyranose) . Generally, the chiroptical properties of artificial polymers depend on several other factors such as the presence of stereoregular secondary structures and the chirality of the repeating units .…”
Section: Resultsmentioning
confidence: 99%
“…Optical active polymers were synthesized by using chiral initiators [99,100] or chiral monomers [100,101]. The polymerization of the studied systems was in a controlled way though the polydispersity index of the obtained optical active polymers was slightly larger than that in normal cases.…”
Section: Functional Polymers Prepared Via Controlled/ "Living" Radicamentioning
confidence: 99%
“…Wang et al [203] studied the optical activity of homopolymers and block copolymers obtained from the RAFT polymerization of protected glycomonomer M51. Homopolymerizations of M51 were carried out in in the presence of R12 (toluene, 90 °C, 50 h) and showed a hybrid evolution of molar mass with conversion, with M n reaching a plateau at ~40% conversion (Entry 240, Table 3).…”
Section: Styrenic Monomersmentioning
confidence: 99%
“…Al-Bagoury et al [177] reported the RAFT polymerization of isopropylidene protected D-glucofuranose methacrylate M13 and D-fructopyranose methacrylate M45 in mini-emulsion. Polymerizations were conducted at 70 °C in a mixture of hexadecane/H 2 O/SDS/NaHCO 3 using three different dithiobenzoate-type RAFT agents (R9, R10 and R11; Entry 190,[201][202][203][204] Table 3). Big deviations of molar masses with respect to their theoretical values were observed in all cases and the best results were obtained using R9 (Đ  1.25, M n /M n,th < 2.7).…”
Section: (Meth)acrylate Monomersmentioning
confidence: 99%